Proposed Approach to Increase the Reliability of Wireless Sensor Networks through Dijkstra’s Algorithm - Jasim Abd Hashim Yaqin; Talib Hasson Saad (SHS Web of Conferences)
This study aims to improve the performance of wireless sensor networks (WSNs) using Dijkstra’s algorithm. WSNs are vital in applications like environmental monitoring and industrial processes, requiring efficient data flow and power management to extend their operational life. Dijkstra’s algorithm is implemented to find the shortest paths between nodes, enhancing energy efficiency, network longevity, and data access speed at minimal cost. Key nodes are selected based on energy levels and proximity to key locations to facilitate data collection and transmission to the main hub, reducing the workload on other sensors and conserving energy. The algorithm also identifies alternative routes if multiple sensors share the same shortest path, reducing congestion, data loss, and interference. Extensive testing shows that Dijkstra’s algorithm significantly improves sensor reliability, and data transmission speed, and reduces message loss compared to unregulated operation. This research confirms Dijkstra’s algorithm’s effectiveness in enhancing WSN functionality, particularly in energy conservation and sustained long-term performance. Implementing Dijkstra’s algorithm enables WSNs to operate more efficiently and effectively, meeting energy conservation requirements while ensuring smooth long-term operation.